A evangelização carismática católica na universidade: o "sonho" do Grupo de Oração Universitário - Gabriel, Eduardo (2005)
The study carried by this research shows the main religious strengthens in the charismatic catholic protestant dynamic in the university. The responsible group for this protestant activity is Grupo de Oração Universitário GOU (University Pray Group) which has as national organization Projeto Universidades Renovadas PUR (Renewed Universities Project) as one of the ministries of Renovação Carismática Católica RCC (Catholic Charismatic Renewal) in Brazil. In the beginning of 1990 a charismatic student from Universidade Federal de Viçosa (Federal University of Viçosa), said to have had a dream of seeing the university full of Jesus doctrine while he was praying in his bedroom. At Seara of 94 (Viçosa RCC Carnival Camp), he organized a seminary named RCC and University where he showed the pray groups first ideas in the university. This is the initial landmark of the Grupo de Oração Universitário, which are presented all over the country with more than 700 GOUs in a lot of private and public universities, and it is already present in some Latin American countries. This current research tries to describe the social meaning of these protestant Dreams in the academic environment and the consequent religious power disputes which are produced inside RCC. It must be detached that GOU has been a notable space for the charismatic universities socialization and also has provided specialized majored people to the RCC communities.